The The Effect of the RADEC Learning Model on Students' Critical Thinking Skills: Case Study of the RADEC Learning Model in High Schools - Veby Turambi; Linda Dwi Saputri (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2026)
The study utilized a quasi-experimental design featuring pretest-posttest with control groups, involving 71 eighth-graders divided between RADEC experimental and conventional control classes. Analysis revealed a significant gain in critical thinking abilities in the experimental group, confirmed by a paired t-test p-value of 0.000 < 0.05. The RADEC model proved effective by promoting active student involvement in grasping and critically applying math concepts, making it a recommended innovative approach for enhancing junior high school mathematics education.